Engagement of Regional Stakeholders in Territory Marketing of Latvian Regions - IGNATYEVS, Sergeys; DIEGTIAR, Oleg A.; OSYPENKO, Krystyna V.; GAPONIUK, Olga I.; OMELCHENKO, Vladimir Ya.; CHERKASOV, Andrii V. (Journal of Advanced Research in Law and Economics; Vol 9 No 6 (2018): JARLE Volume IX Issue 6(36) Fall 2018, 2019)
This article is aimed at empirical establishment of the role of territory marketing in strategic development of Latvian regions from the point of view of regional stakeholders – population, entrepreneurs and the heads of local governments. The potential of regional development is characterized by the flows of strategic resources, which on the basis of resource approach concept form methodological base of strategic, i.e. long-term, development of regions instead of the short-term one. The results of the author’s empirical research showed that the significance of marketing factors, i.e. factors which were created by people in the course of purposeful market activity, was much higher than the significance of non-marketing factors. At the same time, non-marketing factors were much better developed in Latvian regions than marketing factors and it was a practical economic problem, which hindered strategic development of Latvian regions. The authors offer to use a new index, i.e. real marketing force of the factor, and have developed a new scientific product which is an assessment of real marketing force of some factors for Latvian regions. It can be used by specialists and practitioners in the sphere of regional policy and development to assess, monitor and use such tools of territory marketing, which are based on regional stakeholders’ opinion as the framework of legitimacy of these tools.